A la sombra de los mallkus. Tradición oral, ritualidad y ordenamiento del paisaje en una comunidad de Nor Lípez (Potosí, Bolivia) - Gil García, Francisco M. (Revista Española de Antropología Americana, 2008)
This paper shows an ethnography of the two mountains guardians of a community in Nor Lipez (Potosi, Bolivia), paying attention to their prominence in oral tradition and landscape management. First of all, I analyse a group of tails about those I will call «mythic landscape» of this two both mountains, dated from an immemorial time and related to an Inca civilizing an anthropomorphic landscape in conflict. Then, considering the spatial implications of the annual ritual for drawing to the rain celebrated in this community, I point out different lines in order to define the «landscape rituality» unfolded around this two both mountains.